Pengaruh Penggunaan Media Pembelajaran terhadap Hasil Belajar Matematika - Amilatul Ummi; Aprilia Sukma Dewi; Astina Rahmawati; Silviana Wahidayani (Pendidikan Matematika FKIP Universitas Mataram, 2023)
Learning media is one means that can increase effectiveness and efficiency teaching and learning activities. The purpose of this study was to examine the influence of media use learning on student learning outcomes in mathematics. Data collected through related journals for review. The method used in this research is SLR (Systematic Literature Review) method. Researchers collect accredited national journal articles sourced from Google Scholar. Articles that 18 national journal articles were used in this study Obtained from google scholar. Articles that are collected are only articles that published in the period 2015-2023. The results of the research show that the use of media learning in learning mathematics is very influential to arouse interest and motivation of students and have an impact on student learning outcomes.